“Drunk People Are on a Different Level”: A Qualitative Study of Reflections From Students About Transitioning and Adapting to United Kingdom University as a Person Who Drinks Little or No Alcohol - Cook, Elspeth; Davies, E. Bethan; Jones, Katy A. (Frontiers in Psychology, 2022)
Background Though sobriety in young people is on the rise, students who drink little or no alcohol may experience social exclusion at University, impacting well-being. We aim to understand the social experiences of United Kingdom (UK) undergraduate students who drink little or no alcohol. Methods A mixed-methods study using semi-structured, one-to-one interviews and the 24-Item Social Provisions Scale and Flourishing Scale with 15 undergraduate students who drink little or no alcohol. Descriptive statistics are presented for quantitative data and thematic analysis for qualitative. Results Eight main themes and four subthemes were generated from thematic analysis summarised in two sections ‘views of drinkers from non-drinkers’ and ‘how peer pressure feels and how people deal with it.’ The initial transition to University represented a challenge, where participants struggled to find their ‘true’ friends. However, students generally had high levels of social provision, well-being and enjoyed close friendships with fewer casual acquaintances. All students experienced some kind of peer pressure (of a varying extremity) and developed coping strategies when in social situations involving alcohol. Fear of missing out on the ‘typical’ University experience heightened self-imposed expectations to drink. Despite participants acknowledging their counter-normative behaviour, some felt they were subject to stigmatisation by drinkers, doubting their non-drinker status, causing feelings of exclusion or being ‘boring.’ Their desire to ‘be like everyone else’ exposed some insight into the negative stereotypes of sobriety, including frustration behind alcohol’s status elevation. Conclusion Students adopt strategies to minimise peer pressure and to fit in. Future research should interrogate drinkers’ perceptions of their sober peers to deepen understanding, better break down ‘us and them,’ and mitigate future expectations within the University drinking culture.